Analysis of Farmer Relocation Selection Behavior Based on Bayesian Network. (14th September 2022) - Li, Song; Guo, Yanbo
Abstract : The study of farmers' migration choice behavior can reflect people's needs for the future living environment from the side and has practical and important guiding significance for adjusting and improving the focus of future development. In order to make a detailed analysis of the prediction of migrant workers' behavior in cities, this paper studies the internal mechanism of the change of commuters' commuting patterns under the background of urban suburbanization. Using Bayesian network, this paper establishes a model of commuting mode transfer of urban immigrants, taking personal and family attributes as control variables. The influence of factors such as migration attributes and changes in building environment perception before and after migration is analyzed. Based on the survey data, a Bayesian network of farmers' land use behavior is established by using Bayesian network method to investigate the choice of farmers' migration direction. In the research process of migration direction, the research structure shows that 60.1% of farmers want to stay in the countryside, rather than migrate through Bayesian network algorithm. The results of regression analysis by establishing a multivariate logistic model show that there is a strong willingness to choose small towns and large cities. However, the willingness to choose not to relocate to local villages is relatively weak.